Navigating Online Assessments in Post-Pandemic Education: Challenges and Strategies - Afliani, Nia; Ventje Jany Kalukar; Bibit Suhatmady (Borneo Educational Journal (Borju), 2024)
This research aims to describe the use of online assessment by English lecturers in the post-pandemic Covid-19 period. Specifically, this research seeks to identify the challenges faced and how to manage them. The research used qualitative descriptive research focusing on interviews and documentation with lecturers at Universitas Widya Gama Mahakam Samarinda. The findings revealed that lecturers used various platforms including YouTube, Google Drive, SPADA, Instagram, and Facebook. The challenges found in this research were varied due to the hybrid nature of post-pandemic teaching and learning. Challenges faced by lecturers included behavioral issues such as student discipline, plagiarism, password knowledge, and attendance, as well as technical issues such as students' internet access. To manage these challenges, lecturers implemented strict rules against plagiarism, set clear deadlines, and provided rewards like gamification. They also encouraged students to use their names as usernames and passwords and explained the features of the Learning Management System (LMS) to those unfamiliar with it. Additionally, lecturers shared internet data with students to address technical problems. Overall, the research found that online assessment appears to be a solution to meet the needs of lecturers and students, making teaching and learning accessible everywhere, effective, and reaching the target material taught for one semester.